'Steep learning curves' to 'Smooth Sailing': A reappraisal of telegenetics amidst the COVID‐19 pandemic. Issue 4 (6th August 2021) - Mueller, Rebecca; Schindewolf, Erica; Williams, Samantha; Jay Kessler, Lisa
Abstract: The COVID‐19 pandemic has pushed medical providers to trial telemedicine on a scale that lacks precedent. In genetic medicine, nearly overnight genetics providers were asked to transition to telemedicine platforms, irrespective of their previous experience with these modalities. This push to telegenetics prompted a reappraisal of the practice, as genetics providers learned firsthand about the feasibility, benefits, and drawbacks of telegenetics and telesupervision, all of which raise questions about the potential incorporation of these platforms beyond the pandemic. Adding to nascent literature on the transition to telegenetics amidst the COVID‐19 pandemic, we aimed to evaluate provider experiences and preferences with respect to telegenetics through qualitative semi‐structured interviews with genetics providers. Nineteen providers from seven institutions participated in a semi‐structured interview focused on the rapid shift to telegenetics, the benefits and drawbacks of the practice, experiences supervising students on virtual platforms, and providers' preferences. We employed a qualitative methodology so that providers working across diverse subspecialties could expand upon previously reported benefits and drawbacks. Qualitative data revealed the nuanced benefits of telegenetics which included overcoming geographic, spatial, and temporal barriers to care as well as greater involvement of patients' family members in sessions. In addition, the data indicated drawbacks related to additional tasks such as completing paperwork electronically and facilitating the collection of specimens from patients' homes. Interviews with providers from different subspecialties revealed how telegenetics may be uniquely useful for particular subspecialties, patient populations, or clinics for whom the aforementioned barriers are more significant. Providers reported that telesupervision made the provision of feedback to students more cumbersome and identified a number of methods for enriching the telesupervision experience. In keeping with previous research, most genetics providers appraised telegenetics as a valuable addition to patient care (68%, N  = 13) and hoped to offer it as an option beyond the pandemic (63%, N  = 12).